Penentuan Produk Unggulan Usaha Mikro Kecil Menengah Sektor Industri Agro di Kabupaten Bogor - Driska Nurizizah Fasyah; Heny K Daryanto; Gendut Suprayitno (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2016)
Structure of business in Bogor District dominated by 99.84% Small and Medium Enterprises (SMEs). The SMEs have a wide variety of products. Agro industry sector is the potential sector for increasing value added to agricultural products. The purposes of this study was to determine the main product of SMEs agro industry sector. The criterias were set out in the Regulation of the Ministry of Home Affairs of Republic of Indonesia Number 9 of 2014. The study was conducted by using in-depth interview, fill out questionnaire with experts and secondary data. The tools used to analyze the main product is Analytical Hierarchy Process (AHP) and Exponential Comparative Method (MPE). The result show that the most potential product to be main product of SMEs agro industry sector in Bogor District is nutmeg juice. Implications of this study are; (1) establish nutmeg juice as a main product of small medium agro-industry in medium-term development plan of Bogor Distric; (2) the government need to develop the market availability with intensive marketing and partners cooperation, increase quality and productivity of the plantation through cultivation techniques training to increase efficiency, improve the labour skills by providing training